Pelatihan Pemanfaatan Teknologi Infromasi sebagai Strategi Pengembangan Motivasi Guru dalam Meningkatkan Pembelajaran - Nur, M Adnan; Namruddin, Respaty; Arsia, Seni; Wardhani, Nurilmiyanti; Idris, Nur Idil Fitri (Perkumpulan Kualitama Edukatika Indonesia, 2024)
Technological developments require teaching staff to adapt to avoid gaps in information and digital technology knowledge between teaching staff and students because this gap can affect the success of the teaching and learning process. This training was carried out to increase the knowledge and abilities of teaching staff in the field of information technology. This activity begins with the planning stage by determining the needs and location of implementation. This activity was carried out at the YPKK Limbung Vocational School, Gowa Regency. In the preparation stage, the material is prepared based on needs, namely discussing learning strategies using information technology and using the Canva, Powtoon and ChatGPT applications. The target participants for this training are 40 people consisting of teaching staff and education staff. Evaluation is carried out through discussions and questions and answers at each material session. Based on the results of the activity, 38 participants attended. Participants were very enthusiastic about taking part in the training which could be seen from the participants' activeness in discussions and questions and answers. It is hoped that the discussion of topics related to the use of information technology will be able to increase the knowledge and abilities of teaching staff in using technology, especially in the teaching and learning process.